Prototipe Robot Beroda Pengantar Barang di Industri Menggunakan Kontrol Personal Komputer - Mohd Iqbal (Prosiding SISFOTEK, 2019)
In Indonesian on general the process of delivering and moving goods is still done manually. In contrast to developed countries such as America, Japan and China that have created sophisticated robots with various functions that are useful to help work or activities to move or deliver goods from the warehouse to the production area or vice versa in the industrial world. With this research, it will be able to make goods delivery robots in the industry with line follower and remote robots with remote control systems. So that it can implement goods delivery systems in the robot-based industry.